An Impact Analysis of Damage Level caused by Malware with Dynamic Analysis Approach - Anugerah, Christopher Arden; Jadied, Erwid Musthofa; Cahyani, Niken (School of Computing, Telkom University, 2024)
Malware, short for malicious software, is software or code specifically designed to damage, disrupt computer systems, or gain unauthorized access to sensitive information. Based on type classification, one of the well-known types of malware is ransomware. Usually, ransomware will encrypt the files on a computer system and then demand a ransom from the owner of the computer system so that the owner can regain access to the encrypted files. Sometimes in some cases, ransomware is able to delete files without input from the computer system owner. This research includes the analysis process of three ransomware samples that are known for successfully causing losses to many computer systems throughout the world, namely WannaCry, Locky, and Jigsaw, using a dynamic approach and the use of tools to track the processes carried out by the ransomware. The purpose of this research is to determine which of the three samples has the highest to lowest level of damage based on metrics based on file access capabilities and file modification capabilities for various types of files such as system files, boot-related files, program files, etc. The findings of this research indicate that WannaCry has the highest impact followed by Locky and then Jigsaw.